Relationship Between Community Knowledge and the Utilization of Medicinal Plants Among the Moya Community in the Gunung Gamalama Region, Indonesia - Yusri Juma; Tamalia; Zulkifli I. Tuara; Rasmi Hi Panu; Fahrun Yamin (Academy of Social Science and Global Citizenship Journal, 2026)
The use of medicinal plants represents an important component of local wisdom that continues to be practiced by communities across Indonesia, including the Moya community living in the Gunung Gamalama area, Ternate City. This study aimed to examine the relationship between community knowledge levels and the utilization of medicinal plants, as well as to document the diversity of medicinal plant species used by the Moya community. A quantitative approach with a correlational survey design was employed. Data were collected through structured interviews and questionnaires administered to 25 respondents selected using purposive sampling. Descriptive and inferential statistical analyses were performed using Pearson’s Product-Moment correlation and simple linear regression. The results revealed that the mean knowledge score of respondents was 75.84 ± 11.48, while the mean medicinal plant utilization score was 78.28 ± 11.47. Pearson correlation analysis demonstrated a very strong and significant positive relationship between community knowledge and medicinal plant utilization (r = 0.999; p < 0.05). Regression analysis indicated that community knowledge accounted for 99.74% of the variation in medicinal plant utilization. Ethnobotanical inventory documented 25 medicinal plant species belonging to 17 plant families, with leaves being the most frequently utilized plant part. These medicinal plants were commonly used to treat various health conditions, including diabetes, hypertension, malaria, digestive disorders, skin diseases, and coughs. The findings highlight the pivotal role of community knowledge in sustaining the utilization of medicinal plants while simultaneously supporting the preservation of local wisdom and biodiversity in the Gunung Gamalama region.